PENGOLAHAN LIMBAH TERNAK DAN PERTANIAN UNTUK MEMBERIKAN NILAI TAMBAH MENUJU KETAHANAN PANGAN - Dewi, Riana Rachmawati; Dughita, Putri Awaliya; Rois, Dimas Ilham Nur; Ariani, Siska; Hasanah, Aini Nur (LPPM Universitas Bina Bangsa, 2024)
The majority of residents in Suruh Village, Karanganyar Regency work as farm laborers, farmers, breeders and traders. Farmers are starting to have difficulties due to the lack of supply of chemical fertilizers. It turns out that climate change is increasingly extreme, one of the triggering factors is the high levels of substances that are still present in livestock waste, so efforts need to be made to process them. Farmers who do not understand the process of making organic fertilizer, fermented hay and cow candy hope that someone will help to deal with this long-standing problem. Mounting livestock waste and unprocessed dry straw have the potential to become problems in the future. The Uniba Surakarta PKM team with the 2024 PKM grant is trying to help provide solutions to existing problems with training and practice in making organic fertilizer, fermented straw and cow candy. It is hoped that after this activity is completed, the community around the village will be able to process cattle, goat and straw waste so that it has more nutritional value as well as cow candy to increase the strength of the cow's activities. Group members who have been trained will be given bacterial material so they can practice it at home and start applying the results to their plants and livestock, cattle and goat